2007
DOI: 10.1002/mrd.20715
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking cyclin‐dependent kinase inhibitor p19Ink4d show strain‐specific effects on male reproduction

Abstract: p19(Ink4d) is a member of the INK4 family of cyclin-dependent kinase inhibitors, which are important negative regulators of the G1-phase cyclin-dependent kinases CDK4 and CDK6. On a mixed C57BL/6 x 129P2/OlaHsd background, mice deficient for p19(Ink4d) exhibited defects in male reproductive function including testicular atrophy, alteration in serum follicle stimulating hormone, qualitative increase in germ cell apoptosis, and delayed kinetics of meiotic prophase markers (Zindy et al., 2001. Mol Cell Biol 21:32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…4A). Though the testes of p19 Ϫ/Ϫ male mice were slightly smaller than those of WT mice, p19-deficient males were fertile, which is in agreement with previous findings (27,28,40). After monitoring a cohort of 24 p19 Ϫ/Ϫ , 9 p19 ϩ/Ϫ , and 15 wild-type mice for 27 months, we found that 14 (58.3%) p19 Ϫ/Ϫ and 3 (30%) p19 ϩ/Ϫ mice spontaneously developed tumors, whereas only 2 (13.3%) WT mice displayed tumors at a similar age ( Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…4A). Though the testes of p19 Ϫ/Ϫ male mice were slightly smaller than those of WT mice, p19-deficient males were fertile, which is in agreement with previous findings (27,28,40). After monitoring a cohort of 24 p19 Ϫ/Ϫ , 9 p19 ϩ/Ϫ , and 15 wild-type mice for 27 months, we found that 14 (58.3%) p19 Ϫ/Ϫ and 3 (30%) p19 ϩ/Ϫ mice spontaneously developed tumors, whereas only 2 (13.3%) WT mice displayed tumors at a similar age ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…p19 is highly and ubiquitously expressed in both fetal and adult tissues (24), and loss or downregulation of p19 is frequently detected in human hepatocellular carcinoma (25), testicular germ cell tumors (26), glioblastoma, leukemia, and lung adenocarcinoma (Oncomine TCGA data set; https://www .oncomine.org/resource/). Paradoxically, disruption of p19 in mice by insertion of a LacZ-Neo cassette into exon 2 results in a relatively minor phenotype of testicular atrophy with no tumor development (27,28). The pituitary gland is a central endocrine organ that controls growth, reproduction, and metabolism.…”
mentioning
confidence: 99%
“…Ink4d KO mice studied, two displayed atrophied seminiferous tubules (Buchold et al 2007). Unfortunately, the authors did not measure Cdk4 expression levels.…”
Section: Characterization Of Bmyc Knockout Micementioning
confidence: 99%
“…The ANT4 protein is known to be specifically expressed during spermatogenesis and our results provide a first validation to our computational analysis of promoter sequences: several genes involved in spermatogenesis share with the ANT4 gene particular strings in their promoter and some of these strings (matrices from the V$EBOX and V$HIFF families) are known to be specifically involved in the glycolytic pathway. The last identified genes encode for proteins with different functions: cell cycle progression (CDK4, (Buchold et al, 2007)), cell growth (IGF2BP3 and IGF2R, (Nielsen et al, 1999)), or meiosis (RMND1) which could be associated with spermatogenesis. The presence of the previously proposed E2F6-binding element (Kehoe et al, 2008), which is found in the promoters of genes involved in mouse meiosis, was not used in our analysis: This E2F6-binding element is localised downstream the two proposed transcription start sites in positions 128 651 532 (EnsEMBL) and 128 651 555 (Eldorado) and thus could not be considered as a valid regulatory sequence.…”
Section: Transcriptional Regulation Of the Ant4 Genementioning
confidence: 99%